A conceptual model for performance crises in team sport: a narrative review - Buenemann, S.; Raue-Behlau, C.; Tamminen, K. A.; Tietjens, M.; Strauss, B. (International Review of Sport and Exercise Psychology, 2025)
In the present paper, we outline a conceptual model for performance crises in sports teams. We derive a definition of team performance crisis from conceptualizations from other research areas (economics, communications sciences, etc.) and stress theories. Combined with sport psychological literature, this knowledge is adapted to match the specifics of team sports. We define a team performance crisis as continuous underperformance across games, accompanied by team members` threat states, and the inability of a team to cope, resulting in low team functioning. The empirically testable crisis model represents a team performance crisis as a downward spiral with the severity of the crisis determined by how far along the spiral the team has come. There are different stages: crisis predispositions (stage 0), a crisis trigger (stage 1), and the further crisis process (stage 2). While stage 1 depicts what characteristics of a situation have the potential to trigger threat states, stage 2 represents how this leads to the inability to break free. After proposing the model, we differentiate it from other constructs examining the phenomenon of performance deviations and why they are insufficient in explaining lasting underperformance in teams. We provide directions for future research and conclude with practical implications.